RETRACTED: Sibuh et al. The Emerging Role of Epigenetics in Metabolism and Endocrinology. Biology 2023, 12, 256 - Belay Zeleke Sibuh; Sameer Quazi; Hrithika Panday; Ritika Parashar; Niraj Kumar Jha; Runjhun Mathur; Saurabh Kumar Jha; Pankaj Taneja; Abhimanyu Kumar Jha (Biology, 2025)
The Editorial Office of Biology retracts the paper entitled “The Emerging Role of Epigenetics in Metabolism and Endocrinology” [...]